Dispersoid evolution in Al–Zn–Mg alloys by combined addition of Hf and Zr: A mechanistic approach - V. Wessely; U. Töpfer; I. Basu; R.E. Schäublin; S. Pogatscher; P.J. Uggowitzer; J.F. Löffler (Materials & Design)
Coherent Al3X-type L12-structured dispersoids have the potential of effectively stabilizing the grain structure and increasing strength. This concept has been successfully demonstrated for non-hardenable and rapidly solidified Al alloys. In precipitation-hardened Al alloys, effective dispersoid addition requires both controlling their high-temperature stability and minimizing their impact on precipitation hardening. The current study focuses on dispersoid-modified AlZn5.0Mg1.2 alloys, which exhibit MgZn precipitation upon age-hardening and include less than 1 wt% of Zr and Hf for dispersoid formation. Heat treatments between 350 °C and 500 °C for varying times were applied to evaluate dispersoid formation, thermal stability and the related strengthening potential. The microstructure was assessed using transmission electron microscopy (TEM) and atom probe tomography (APT), and the mechanical response was evaluated by hardness testing. TEM after heating at 500 °C reveals Ostwald ripening for the dispersoids. APT results on the dispersoids reveal a core–shell structure development upon longer annealing times. The Zr–Hf-modified alloy exhibits a higher initial strength than the Zr-modified alloy but the latter displays greater strength retention even after prolonged exposure to 500 °C. This effect is attributed to a destabilization of the mixed Zr–Hf dispersoids that arises from lower enthalpic benefits of Al3Hf formation over Al3Zr.